Probing the transition between seismically coupled and decoupled segments along an ancient subduction interface. (21st June 2015) - Angiboust, Samuel; Kirsch, Josephine; Oncken, Onno; Glodny, Johannes; Monié, Patrick; Rybacki, Erik
Abstract The transition zone at the downdip end of seismic coupling along subduction interfaces is often the site of megathrust earthquake nucleation and concentrated postseismic afterslip, as well as the focus site of episodic tremor and slip features. Exhumed remnants of the former Alpine subduction zone found in the Swiss Alps allow analyzing fluid and deformation processes near the transition zone region (30–40 km paleodepth). The Dent Blanche Thrust (DBT) is a lower blueschist‐facies shear zone interpreted as a fossilized subduction interface where granitic mylonites overlie a metamorphosed accretionary wedge. We report field observations from the DBT region where multiple, several tens of meters thick foliated cataclastic networks are interlayered within the basal DBT mylonites. Petrological results and microstructural observations indicate that the various cataclasis events took place at near‐peak metamorphic conditions (400–500°C, 1.1–1.3 GPa) during subduction of the Tethyan seafloor in Eocene times (42–48 Ma). Some of these networks exhibit mutual crosscutting relationships between mylonites, foliated cataclasites, and vein systems indicating mutual overprinting between brittle deformation and ductile creep. Whole‐rock chemical compositions, in situ 40Ar‐39Ar age data of recrystallized phengite, and Sr isotopic signatures reveal that DBT rocks also underwent multiple hydrofracturing and metasomatic events via the infiltration of fluids mainly derived from the oceanic metasediments underneath the DBT. From the rock fabrics, we infer strain rate fluctuations of several orders of magnitude beyond subduction strain rates (∼10−12 s−1) accompanied by fluctuation of supralithostatic and quasi‐lithostatic fluid pressures (1 ≥ λ > 0.95). DBT brittle‐plastic deformation switches highlight the diversity of deformation processes and fluid‐rock interactions in the transition zone region of the subduction interface.